Comparative Study of Intraocular Pressure Measurements with Airpuff, iCare and Goldmann Applanation Tonometers: Doi: 10.36351/pjo.v37i1.1139 - Mirza, Umair Tariq; Sadiq, M. Usman; Sadiq, M. Irfan; Raza, Ali; Khan, Waseem Ahmed (Pakistan Journal of Ophthalmology, 2020)
Purpose: To compare the difference in intraocular pressure (IOP) measurements by Airpuff, iCare and Goldmann Applanation Tonometers (GAT). Study Design: Comparative analytical study. Place and Duration of Study: Department of Ophthalmology, Mohi-ud-Din Teaching Hospital, Mirpur Azad Kashmir, from June 2020 to August 2020. Methods: Twenty-five patients (50 eyes) were included in this study. IOP was measured in each eye firstly by Airpuff tonometery, then by iCare tonometery and lastly by Goldmann applanation tonometer. Three consecutive readings were taken in each eye. If there was a difference of 2 mm Hg or more among the readings, measurement was repeated. Once we got three readings, their average was taken and analyzed. Comparison of IOP readings between these tonometers was done. Results: Mean IOP was 15.84 ± 2.736 mm Hg with Airpuff Tonometer, 14.48 ± 2.435 mm Hg with iCare Tonopen and 14.74 ± 2.489 mm Hg with Goldman Applanation Tonometer. The difference between the mean Airpuff and Goldman Applanation Tonometer readings was 1.10 mm Hg which was not statistically significant (p-value = 0.083). The difference between the mean Goldman Applanation Tonometer and iCare Tonopen readings was 0.26 mm Hg which is also not statistically significant (p-value = 0.867). But, the difference between the mean iCare Tonopen and Airpuff Tonometer readings was -1.36 mm Hg which was statistically significant (p-value = 0.02). Conclusion: It is concluded that IOP readings taken by iCare Tonopen and Airpuff Tonometer are comparable to those taken by Goldman Applanation Tonometer and iCare Tonopen underestimates the IOP when compared with Airpuff Tonometer. Key Words: Airpuff Tonometer, Glaucoma, Goldmann Applanation Tonometer, iCare Tonometer, Intraocular Pressure.